PRESERVICE TEACHERS' VIEWS ABOUT NATURE OF SCIENTIFIC KNOWLEDGE DEVELOPMENT: AN INTERNATIONAL COLLABORATIVE STUDY - Liang, Ling L.; Chen, Sufen; Chen, Xian; Kaya, Osman Nafiz; Adams, April Dean; Macklin, Monica; Ebenezer, Jazlin (Springer, 2009)
This article presents the findings of an international collaborative investigation into preservice teachers' views on the nature of scientific knowledge development with respect to six elements: observations and inferences, tentativeness, scientific theories and laws, social and cultural embeddedness, creativity and imagination, and scientific methods. A total of 640 preservice teachers, 209 from the United States, 212 from China, and 219 from Turkey, participated in the study. The survey Student Understanding of Science and Scientific Inquiry (SUSSI), having a blend of Likert-type items and related open-ended questions, was used to gain a fuller understanding of the preservice teachers' views of the nature of scientific knowledge development. Across the three countries, the participants demonstrated better understanding of the tentative NOS aspect but less understanding of the nature of and relationship between scientific theories and scientific laws. The Chinese sample scored highest on five of the six Likert sub-scales, the USA sample demonstrated more informed views on observation and inference, and the Turkish preservice teachers possessed relatively more traditional views in all six NOS aspects. Conclusions and limitations of the present study as well as implications and recommendations for future studies, are also discussed.
Keywords: international collaborative study; nature of science; nature of scientific knowledge development; pre-service science teacher education